2019
DOI: 10.1039/c9dt00570f
|View full text |Cite
|
Sign up to set email alerts
|

Four-component relativistic 31P NMR calculations for trans-platinum(ii) complexes: importance of the solvent and dynamics in spectral simulations

Abstract: We report a combined experimental–theoretical study on the 31P NMR chemical shift for a number of trans-platinum(ii) complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…The results shown here indicate that it cannot be conclusively determined whether the experimentally observed spectra belong to the o ‐benzyne molecule or to an adduct with an aromatic ring of the hemicarcerand. An investigation of the conformational and solvent effects combining molecular dynamic simulations and average NMR chemical shift calculations (similar to a recent study on a platinum complex) is currently underway for the incarcerated o ‐benzyne.…”
Section: Resultsmentioning
confidence: 99%
“…The results shown here indicate that it cannot be conclusively determined whether the experimentally observed spectra belong to the o ‐benzyne molecule or to an adduct with an aromatic ring of the hemicarcerand. An investigation of the conformational and solvent effects combining molecular dynamic simulations and average NMR chemical shift calculations (similar to a recent study on a platinum complex) is currently underway for the incarcerated o ‐benzyne.…”
Section: Resultsmentioning
confidence: 99%
“…128 The work of Hrobarik et al on uranium complexes 129 that predicted the record positive 1 H shifts of more than +100 ppm for uranium(VI) hydride complexes, and the related large 13 C shifts in organouranium(VI) complexes, highlighted large discrepancies between 4c ReSpect and 2c ZORA ADF computations that have also been observed elsewhere. 130,131 Whereas the ZORA results were used in the initial work, it was subsequently found that the ADF 2c ZORA implementation had been lacking the exchange-correlation kernel, thus explaining the observed discrepancies. Using a modified ADF implementation with an approximate kernel gave much better agreement between the 2c ZORA and 4c ReSpect DKS shift calculations for both of the above-mentioned studies of TLI, confirming the correctness of the kernel in ReSpect and correcting the preferred exact-exchange admixture to be used in hybrid functionals to predict such SO-induced shifts when the XC kernel is present.…”
Section: A Nmr Applicationsmentioning
confidence: 99%
“…In addition to the level of theory and relativistic effects, an important source of error in the NMR chemical shift calculations of transition-metal complexes arise from neglect of the solvation shell effects and/or conformational flexibility. 19 22 For this reason, we have additionally explored the solvent effects and dynamical behavior of complex 1 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Although several individual effects can influence the quality of the calculated NMR parameters, various studies have demonstrated that the inclusion of both relativistic and solvent effects is essential for proper prediction of the NMR chemical shifts in transition-metal complexes. 19 22 …”
Section: Introductionmentioning
confidence: 99%